Mediation effect and metabolic pathways of gut microbiota in the associations between lifestyles and dyslipidemia - Lijun Zeng; Bin Yu; Peibin Zeng; Zhuoma Duoji; Haojiang Zuo; Jian Lian; Tingting Yang; Yingxue Dai; Yuemei Feng; Peng Yu; Jiqi Yang; Shujuan Yang; et al. (npj Biofilms and Microbiomes)
Abstract Whether the role of gut microbial features lies in the pathways from lifestyles to dyslipidemia remains unclear. In this cross-sectional study, we conducted a metagenome-wide association analysis and fecal metabolomic profiling in 994 adults from the China Multi-Ethnic cohort. A total of 26 microbial species were identified as mediators between lifestyle factors and risk for dyslipidemia. Specifically, the abundance of [Ruminococcus] gnavus mediated the associations between lifestyles and risks for dyslipidemia, elevated low-density lipoprotein cholesterol, elevated total cholesterol, and elevated triglycerides. [Ruminococcus] gnavus, Alistipes shahii, and Lachnospira eligens were replicated to be associated with dyslipidemia in an external validation cohort. The potential metabolic pathways included arachidonic acid, bile acid, and aromatic amino-acid metabolism.